Prevalence and determinants of HealthHub app utilization among community-dwelling adults in Singapore. - Mahir Bakulkumar Goda; Alexander Shao-Rong Pang; Benedict Ding Chao Ong; Fang Nian Joanne Lim; Alvin Kian Wei Tan; Lay Hoon Goh (PLoS ONE)
Introduction Singapore's aging population, projected to reach 18.7% by 2030, will increase chronic disease burden and strain healthcare resources. Digital health technologies, like Singapore's HealthHub Application (HHA), are crucial for improving patient outcomes and healthcare delivery. However, the use of HHA among older adults in Singapore remains poorly understood. This study aimed to examine the prevalence of HHA use among community-dwelling Singaporeans and identify factors associated with its use. Methods A cross-sectional survey was conducted in a public housing estate in Singapore, using random sampling to select housing units. Eligibility criteria included being a Singaporean or permanent resident, aged 40 years and above, possessing English proficiency, and absence of cognitive impairment. Participants completed a self-administered electronic questionnaire in English covering socio-demographics, health literacy, use of digital health technologies, and perceptions of HHA. Responses were categorized and analysed using descriptive statistics, univariate analysis, and multivariable logistic regression. Results Of the 422 completed responses, 216 (51.2%) of participants reported HHA use. Higher HHA usage was associated with younger age, higher education levels, and greater self-perceived knowledge of health management. Older adults, particularly those aged 70 and above, and participants with secondary education or below had significantly lower HHA usage compared to their counterparts. Additionally, better health literacy as measured by positive perceptions of health knowledge were significantly associated with HHA usage. Conclusion The adoption of digital health technologies like HHA is lower among older adults with lower education and health knowledge in Singapore. Targeted efforts to improve digital skills, awareness, and usability are needed to promote HHA uptake and support equitable healthcare access in an aging population.